Impacts of Energy Price Subsidy Reform on MSMEs and Their Adjustment Strategies: a Story from Indonesia - Tulus T.H. Tambunan (International Journal of Small and Medium Enterprises and Business Sustainability, 2016)
This is an exploratory study at the micro level which tried to explore the impacts of energy price increases on micro, small and medium enterprises (MSMEs) in Indonesia. More specifically, it aimed to answer the following research question: what was the impact of energy price increases occurred before on MSMEs, and which measures they have taken to cope with the impact? For that purpose, it has adopted a qualitative approach with three methods of analysis: i) desk study; (ii) a series of surveys of a total of 193 respondents (owners/managers of MSMEs) in various cities in Java and West Sumatera, and (iii) focus group discussions (FGDs). Findings of the study suggest that the overall impacts of energy price increases on MSMEs depend on their current capacity to mitigate the impact. However, the type of mitigation varies across MSMEs, depending various factor, including the current availability of financial resources and current market condition which determines to what extent the MSMEs can increase their selling prices or reduce the size of their made goods without losing their customers or market shares.